I remember : eighty years of black entertainment, big bands, and the blues : an autobiography - Bernhardt, Clyde E. B. (University of Pennsylvania Press, 1986)
I Remember is a first-hand account of the world of black American music told by a man who has been part of that world for eighty years. Clyde E.B. Bernhardt worked with a number of bands, including King Oliver, Marion Hard, Cecil Scott, the Bascomb Brothers, and Joe Garland. He started his own band, the Blue Blazers, in 1946 and formed the Harlem Blues and Jazz Band in 1972. The book is a primary document that provides information about a part of the history of American music for which there is little documentation.